Elevated striatal dopamine function in immigrants and their children: a risk mechanism for psychosis - Egerton, Alice; Meyer-Lindenberg, Andreas (Schizophrenia bulletin, 2017)
Abstract. Migration is a major risk factor for schizophrenia but the neurochemical processes involved are unknown. One candidate mechanism is through elevation